The flood year 1927 : a cultural history - Parrish, Susan Scott (Princeton University Press, 2018)
The Great Mississippi Flood of 1927, which covered nearly thirty thousand square miles across seven states, was the most destructive river flood in U.S. history. Due to the speed of new media and the slow progress of the flood, this was the first environmental disaster to be experienced on a mass scale. As it moved from north to south down an environmentally and technologically altered valley, inundating plantations and displacing more than half a million people, the flood provoked an intense and lasting cultural response. This text shows how the event took on public meanings. Americans at first seemed united in what Herbert Hoover called a 'great relief machine, ' but deep rifts soon arose.